Retrospective Analysis of Cone Beam Computed Tomography Referrals in a Paediatric and Adolescent Patient Subgroup - GÜMRÜ TARÇIN, BİRSAY (My University, 2022)
Objectives: This study was aimed to evaluate the cone beam computed tomography (CBCT) indications in paediatric and adolescent patients and to investigate their compliance with the guidelines set by the DIMITRA (dentomaxillofacial paediatric imaging: an investigation toward low-dose radiation induced risks) Project. Materials and Methods: CBCT images of paediatric and adolescent patients were selected and evaluated among a total of 12494 CBCT images reviewed retrospectively. Data regarding age, gender, referring department, field of view (FOV), and CBCT indications were recorded. Based on an adaptation of European DIMITRA Project recommendations, CBCT indications were categorized as impacted teeth, trauma, orofacial clefts, dental anomalies, bone pathology, syndromes, and other indications. Follow-up CBCT examinations and incidental findings were also recorded. Data were statistically analyzed at p<0.05 significance level. Results: Most of the 1686 CBCT scans obtained from paediatric and adolescent patients were referred from the Department of Oral and Maxillofacial Radiology (31.2%), followed by the Departments of Orthodontics (25.9%) and Oral and Maxillofacial Surgery (24.6%). The most frequently requested FOV was the maxilla (35.1%) followed by the jaws (maxilla-mandible) (29.3%) and the maxillary canine-incisor region was the most commonly requested region among localised applications (83.1%). The most common indication was impacted teeth (33.5%) followed by bone pathology (32.7%). Follow-up CBCT examinations were recorded mostly for syndromes (33.3%) and orofacial clefts (20.4%). Conclusions: The use of CBCT should be justified on a patient basis and DIMITRA Project recommendations can guide dental professionals in referring CBCT in paediatric and adolescent population. Keywords: cone beam computed tomography, indication, paediatric, adolescent

Amaç: Bu retrospektif çalışmada, pediatrik ve adolesan hastalarda konik ışınlı bilgisayarlı tomografi (KIBT) endikasyonlarının değerlendirilmesi ve DIMITRA (dentomaxillofacial paediatric imaging: an investigation toward low-dose radiation induced risks) Projesi ile belirlenen kılavuza uygunluğunun araştırılması amaçlanmıştır. Gereç ve Yöntemler: Retrospektif olarak incelen toplam 12494 KIBT görüntüsü arasından pediatrik ve adolesan hastaların KIBT görüntüleri seçilmiş ve değerlendirilmiştir. Yaş, cinsiyet, sevk eden bölüm, görüntüleme alanı (FOV) ve KIBT endikasyonlarına ilişkin veriler kaydedilmiştir. Avrupa DIMITRA Projesi önerilerinin modifikasyonuna dayanarak KIBT endikasyonları gömülü dişler, travma, orofasiyal yarıklar, dental anomaliler, kemik patolojisi, sendromlar ve diğer endikasyonlar olarak kategorize edilmiştir. Takip KIBT incelemeleri ve tesadüfi bulgular da kaydedilmiştir. Veriler istatistiksel olarak p<0,05 anlamlılık düzeyinde analiz edilmiştir. Bulgular: Pediatrik ve adolesan hastalardan alınan 1686 adet KIBT görüntüsünün çoğu Ağız, Diş ve Çene Radyolojisi Anabilim Dalı’ndan (%31,2) istenmiş olup, bunu Ortodonti (%25,9) ve Ağız, Diş ve Çene Cerrahisi Anabilim Dalları (%24,6) izlemiştir. En sık istenen FOV maksilla (%35,1) olup, bunu çeneler (maksillamandibula) (%29,3) takip etmiştir. Lokalize uygulamalar arasında en sık istenen bölge maksiller kanin-kesici bölge (%83,1) olarak saptanmıştır. En sık görülen KIBT endikasyonu gömülü dişler (%33,5) olup, bunu kemik patolojisi (%32,7) izlemiştir. Takip KIBT incelemeleri çoğunlukla sendromlar (%33,3) ve orofasiyal yarıklar (%20,4) için istenmiştir. Sonuç: KIBT kullanımı hasta bazında gerekçelendirilmelidir ve DIMITRA Projesi tavsiyeleri diş hekimlerine pediatrik ve adolesan popülasyonda KIBT endikasyonlarında rehberlik edebilir. Anahtar Kelimeler: konik ışınlı bilgisayarlı tomografi, endikasyon, pediatrik, adolesan
Pediatrik ve Adolesan Hasta Grubunda Konik Işınlı Bilgisayarlı Tomografi Endikasyonlarının Retrospektif Analizi
Keywords: konik ışınlı bilgisayarlı tomografi; endikasyon; pediatrik; adolesan; cone beam computed tomography; indication; paediatric; adolescent